2021
DOI: 10.1186/s12884-020-03463-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing knowledge and skills of maternity care professionals regarding neonatal hyperbilirubinaemia: a nationwide survey

Abstract: Background Neonatal hyperbilirubinaemia is a physiologic phenomenon, but, when severe, may cause lifelong disability. Maternity care assistants (MCAs) play an important role in timely recognition of severe neonatal jaundice. We assessed knowledge and skills of MCAs regarding neonatal hyperbilirubinaemia. Methods All Dutch MCAs (n = 9065) were invited to fill out a questionnaire assessing knowledge, expertise, and handling of neonatal jaundice. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Strikingly, in a substantial proportion of neonates being assessed as ‘quite yellow’ or ‘very yellow’, no TcB or TSB was quantified. This observation corresponds with a previous study among MCAs regarding neonatal hyperbilirubinaemia, which showed structural underestimation of TSB levels and common application of a so-called ‘wait-and-see approach’ in visibly jaundiced neonates 30 . Moreover, despite being strongly recommended by the national guideline 4 , TSB was not quantified in two neonates who developed visible jaundice within 24 h after birth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Strikingly, in a substantial proportion of neonates being assessed as ‘quite yellow’ or ‘very yellow’, no TcB or TSB was quantified. This observation corresponds with a previous study among MCAs regarding neonatal hyperbilirubinaemia, which showed structural underestimation of TSB levels and common application of a so-called ‘wait-and-see approach’ in visibly jaundiced neonates 30 . Moreover, despite being strongly recommended by the national guideline 4 , TSB was not quantified in two neonates who developed visible jaundice within 24 h after birth.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, we did not prospectively explore the considerations underlying these decisions. Previous studies indicate that lack of knowledge on guideline recommendations 31 , 32 , and systematic underestimation of the severity of jaundice based on visual assessment likely contributed 30 . Other potential reasons for non-compliance may include a belief that the recommendations in the guideline do not reflect the best care for the neonate (e.g., a healthcare provider may consider the phototherapy thresholds too conservative as evidence on exact phototherapy thresholds is lacking 33 , and TSB quantification is avoided to keep the neonate in primary care), or practical challenges regarding feasibility of guideline compliance in daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, and especially in the home setting, it may take several hours before TSB test result is obtained. Other potential explanations for the delay may be a wait-and-see approach and underestimation of the severity of hyperbilirubinaemia and its potential consequences in otherwise healthy neonates, which has also been shown in a nationwide survey among MCAs 27. ET was performed in only 28% of the neonates, whereas all neonates had a TSB level above ET threshold.…”
Section: Discussionmentioning
confidence: 87%